Turning the hands of time again: a purely confirmatory replication study and a Bayesian analysis - Wagenmakers, Eric-Jan; Beek, Titia F.; Rotteveel, Mark; Gierholz, Alex; Matzke, Dora; Steingroever, Helen; Ly, Alexander; Verhagen, Josine; Selker, Ravi; Sasiadek, Adam; Gronau, Quentin F.; Love, Jonathon; et al. (Frontiers in Psychology, 2015)
In a series of four experiments, Topolinski and Sparenberg (2012; TS) found support for the conjecture that clockwise movements induce psychological states of temporal progression and an orientation toward the future and novelty. Here we report the results of a preregistered replication attempt of Experiment 2 from TS. Participants turned kitchen rolls either clockwise or counterclockwise while answering items from a questionnaire assessing openness to experience. Data from 102 participants showed that the effect went slightly in the direction opposite to that predicted by TS, and a preregistered Bayes factor hypothesis test revealed that the data were 10.76 times more likely under the null hypothesis than under the alternative hypothesis. Our findings illustrate the theoretical importance and practical advantages of preregistered Bayes factor replication studies, both for psychological science and for empirical work in general.